The marine triterpene glycoside frondoside A exhibits activity in vitro and in vivo in prostate cancer. Issue 10 (23rd January 2016) - Dyshlovoy, Sergey A.; Menchinskaya, Ekaterina S.; Venz, Simone; Rast, Stefanie; Amann, Kerstin; Hauschild, Jessica; Otte, Katharina; Kalinin, Vladimir I.; Silchenko, Alexandra S.; Avilov, Sergey A.; Alsdorf, Winfried; Madanchi, Ramin; et al.
Abstract : Despite recent advances in the treatment of metastatic castration‐resistant prostate cancer (CRPC), outcome of patients remains poor due to the development of drug resistance. Thus, new drugs are urgently needed. We investigated efficacy, toxicity and mechanism of action of marine triterpene glycoside frondoside A (FrA) using CRPC cell lines in vitro and in vivo . FrA revealed high efficacy in human prostate cancer cells, while non‐malignant cells were less sensitive. Remarkably, proliferation and colony formation of cells resistant to enzalutamide and abiraterone (due to the androgen receptor splice variant AR‐V7) were also significantly inhibited by FrA. The marine compound caused cell type specific cell cycle arrest and induction of caspase‐dependent or ‐independent apoptosis. Up‐regulation or induction of several pro‐apoptotic proteins (Bax, Bad, PTEN), cleavage of PARP and caspase‐3 and down‐regulation of anti‐apoptotic proteins (survivin and Bcl‐2) were detected in treated cells. Global proteome analysis revealed regulation of proteins involved in formation of metastases, tumor cell invasion, and apoptosis, like keratin 81, CrkII, IL‐1β and cathepsin B. Inhibition of pro‐survival autophagy was observed following FrA exposure. In vivo, FrA inhibited tumor growth of PC‐3 and DU145 cells with a notable reduction of lung metastasis, as well as circulating tumor cells in the peripheral blood. Increased lymphocyte counts of treated animals might indicate an immune modulating effect of FrA. In conclusion, our results suggest that FrA is a promising new drug for the treatment of mCRPC. Induction of apoptosis, inhibition of pro‐survival autophagy, and immune modulatory effects are suspected modes of actions. Abstract : What's new? Prognosis of patients with metastatic castration‐resistant prostate cancer (CRPC) remains poor due to the development of drug resistance. Here, the authors investigated the efficacy, toxicity and mechanism of action of the novel marine compound triterpene glycoside frondoside A (FrA) using CRPC cell lines in vitro and in vivo . They found that FrA inhibits human prostate cancer cells, including those resistant to docetaxel, abiraterone and enzalutamide. Remarkably, FrA simultaneously induces apoptosis and cell cycle arrest and suppresses pro‐survival autophagy. FrA also decreases local tumor growth and metastatic spread in vivo without significant toxicities, with immune‐modulating effects potentially contributing to the activity.